Contemporary Shariah and Legal Pertinent Issues in Cash Waqf Mechanism using Peer To Peer (P2p) Platform in Indonesian Islamic Economics - Akhmad Affandi Mahfudz (Universitas Darussalam Gontor, 2022)
The remarkable growth of financial technology wreaks significant impact to the liquidity of Islamic financial industry. Cash waqf now is perceived as the right instrument to ameliorate the issue of liquidity amid modest effort of financial industry in Indonesia. Cash waqf using P2P (Peer to Peer) platform model now is becoming the untapped potential of business beside social responsibility. However, there are some issues as cash waqf integrated with P2P platform that might lead to another phenomenon of shariah compliance in financial technology. In view of this backdrop, this paper aims to unveil the issue of shariah compliance in contract that used to disburse cash waqf funds using P2P platform model. Second, this paper also deciphers some legal issues that might occur that contrary to the existing law. The paper finds that since the existing regulation including Fatwa considered as general, there is possibility that the practice of P2P shariah deviate from Shariah tenet and wreak some legal issues. In the event of default payment, late charges and early settlement not clearly regulated and no standard. This paper also finds that no such governance standard, risk management, shariah compliance and code of ethics oThe contract inherent in this platform model shall be in line with the tenet of Shariah principles and not only comply with existing regulation. This paper implies that more cash waqf will be generated through this platform model as it is easier and more practical. In addition, financial industry will adhere strictly to shariah compliance aspect as their concern.